Murabahah Contract for Motor Vehicle Financing at CIMB Niaga Auto Finance (CNAF): Perspective on Sharia Banking Law - Sawitri Yuli Hartati S.; Buldani Ridha; Dewi Nadya Maharani; Gatot Efrianto; Setiyono (KRTHA BHAYANGKARA, 2025)
Normatively, the motor vehicle financing agreement at CIMB Niaga Auto Finance (CNAF) already has a strong legal basis. The murabahah contract used has been recognised as valid by DSN-MUI Fatwa Number 4 of 2000 concerning Murabahah and further strengthened by the Compilation of Islamic Economic Law (KHEIS), as well as by Law Number 21 of 2008 concerning Sharia Banking. This affords dual legitimacy, deriving from both sharia law and positive Indonesian law. However, there are discrepancies; the existence of this dishonesty can give rise to an element of gharar (ambiguity) and is contrary to the Fatwa of DSN-MUI and KHEIS, which require information disclosure to avoid prohibited practices. In reality, the settlement of financing disputes at CNAF also shows incompatibility with Sharia principles. The use of the Civil Code as a legal basis for dispute resolution, including the application of late fines, is inconsistent with the DSN-MUI Fatwa. Thus, the existence of a penalty clause and a choice of civil law in the CNAF agreement is normatively contrary to the principles of justice and Sharia compliance. Therefore, improvements are needed to the agreement clauses to align them with the applicable principles and fatwas. This research employs two approaches: a normative juridical and an empirical approach. The normative juridical approach is carried out deductively, focusing on the analysis of relevant laws and regulations. This research falls within the category of literature studies that rely on secondary data.